OPTICAL GEOMETRIC DESIGN OF SMALL MODULAR CYLINDRICAL GEARS WITH ASYMMETRIC PROFILE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article presents specific practical solutions for optimal geometric design of evolvental cylindrical gears with an asymmetric profile of cogs in the context of the basic principle of cog interlocking. In order to achieve unknown until now quality indicators, constructions with a minimum number of cogs and a maximum angle of interlocking are shown, which allow for the production of off-polar gears and significantly increase the gear ratio of the differential and planetary mechanisms. In the process of determining the geometrical parameters of the cogwheels of the gear, the “classical approach” is used by analogy with the parameters of the instrument, necessary for the production of the small-module cogwheels of the gear.